The influence of Brand Image, Product Quality, and Price on Buying Decisions of Nissan Type Livina Cars - Rina Faja Taxvia; Riyadi - Riyadi; Erika - Devie (JOBS (Jurnal Of Business Studies), 2020)
The consumer purchase decisions of Nissan Setiabudi Semarang Dealers to Nissan type Livina cars higher when compared to other types of Nissan cars, which can be seen from the car sales data of Nissan Setiabudi Semarang Dealers. Purchase decisions are influenced by several factors, including brand image, product quality, and price. The purpose of this research was to see the influence of brand image, product quality, and price on the purchase decision of Nissan type Livina cars at Nissan Setiabudi Semarang Dealers. The methods of collecting data were questionnaire, interview, and literature view. The data analysis used was multiple linier regression analysis. The number of samples in the research were 98 consumers. The results shows that the brand image partially had no significant effect on purchase decisions, while product quality and price had significant increase on purchase decisions. Then simultaneously the variables were brand image, product quality, and price had significant effect on purchase decisions. Based on results of multiple linier regression analysis, the equation Y =  1,199 + 0,105X1 + 0,547X2 + 0,222X3. Purchase decisions were explained by the variables of brand image, product quality, and price by 73,7%, while the remaining 26,3% was explained by other variables not examined in this research.